High-level Relatedness among Mycobacterium abscessus subsp. massiliense Strains from Widely Separated Outbreaks - Tettelin, Hervé; Davidson, Rebecca M.; Agrawal, Sonia; Aitken, Moira L.; Shallom, Shamira; Hasan, Nabeeh A.; Strong, Michael; Nogueira de Moura, Vinicius Calado; De Groote, Mary Ann; Duarte, Rafael S.; Hine, Erin; Parankush, Sushma; et al. (Emerging infectious diseases, 2014)
Three recently sequenced strains isolated from patients during an outbreak of Mycobacterium abscessus subsp. massiliense infections at a cystic fibrosis center in the United States were compared with 6 strains from an outbreak at a cystic fibrosis center in the United Kingdom and worldwide strains. Strains from the 2 cystic fibrosis outbreaks showed high-level relatedness with each other and major-level relatedness with strains that caused soft tissue infections during an epidemic in Brazil. We identified unique single-nucleotide polymorphisms in cystic fibrosis and soft tissue outbreak strains, separate single-nucleotide polymorphisms only in cystic fibrosis outbreak strains, and unique genomic traits for each subset of isolates. Our findings highlight the necessity of identifying M. abscessus to the subspecies level and screening all cystic fibrosis isolates for relatedness to these outbreak strains. We propose 2 diagnostic strategies that use partial sequencing of rpoB and secA1 genes and a multilocus sequence typing protocol.